2022
DOI: 10.3390/jcm11237248
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatitis Associated with Atypical Bacterial Pneumonia: Systematic Literature Review

Abstract: Background: Extra-pulmonary features sometimes occur in association with atypical bacterial pneumonia and include neurologic manifestations, diarrhea, rashes, altered liver enzymes, or kidney injury, among other conditions. Acute pancreatitis has been associated with atypical pneumonias since 1973. Methods: We performed a systematic review of the literature in the Excerpta Medica, National Library of Medicine, and Web of Science databases. We retained 27 reports published between 1973 and 2022 describing subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In human medicine, several case reports have described patients with acute pancreatitis associated with Mycoplasma pneumoniae infection. 18 25 The patients typically exhibited respiratory signs as the predominant clinical manifestation, 18,20 which were absent in the cat described here.…”
Section: Discussionmentioning
confidence: 62%
“…In human medicine, several case reports have described patients with acute pancreatitis associated with Mycoplasma pneumoniae infection. 18 25 The patients typically exhibited respiratory signs as the predominant clinical manifestation, 18,20 which were absent in the cat described here.…”
Section: Discussionmentioning
confidence: 62%
“…( 11 13 ). However, reports of secondary acute pancreatitis in patients with a C. psittaci infection are rare ( 3 ), which may be owing to the low incidence of psittacosis, difficulty of its diagnosis, or lack of clinician awareness. Byrom et al ( 14 ) first reported two cases of C. psittaci pneumonia with concomitant acute pancreatitis in 1979.…”
Section: Discussionmentioning
confidence: 99%
“…C. psittaci often induces various extrapulmonary complications, such as acute liver injury, acute renal failure, myocarditis, and meningitis ( 2 ). However, the occurrence of secondary acute pancreatitis in patients with C. psittaci pneumonia has rarely been reported ( 3 ). Common symptoms of psittacosis include severe pyrexia, chills, headache, dyspnea, and cough.…”
Section: Introductionmentioning
confidence: 99%
“…Qualified for the study were individuals on long-term (≥4 weeks) therapy with valproic acid presenting with acute-onset abdominal pain, vomiting or distension and at least one of the following [ 1 , 2 , 3 ]: 1. amylase or lipase values three times or more the upper limit of normal (the normal values recommended in the literature were taken into consideration for communications, which did not include any reference); 2. imaging studies, intra-surgical or autoptic findings disclosing features consistent with an acute pancreatitis.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic alcohol use disorder, gallstone disease, severe hypertriglyceridemia, and hypercalcemia are the most common triggers of acute pancreatitis [ 1 , 2 ]. There is also, but less frequently, an association with genetic factors or with infections of viral (mumps, coxsackievirus, cytomegalovirus, varicella, herpes simplex virus), parasitic (toxoplasma, cryptosporidium, ascaris), fungal (aspergillus), or bacterial (mycoplasma, legionella, leptospira, salmonella) origin [ 1 , 3 ]. Affected patients present with acute-onset severe epigastric and left upper quadrant abdominal pain, usually associated with nausea and vomiting [ 1 ].…”
Section: Introductionmentioning
confidence: 99%